2017
DOI: 10.1017/s1368980017002075
|View full text |Cite
|
Sign up to set email alerts
|

Greater access to healthy food outlets in the home and school environment is associated with better dietary quality in young children

Abstract: The results strengthen the argument for local authorities to increase the number of healthy food outlets to which young children are exposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…There were median (IQR) 46 (33-77) food outlets within 1600 m of schools, ranging from eleven to 124 outlets. There were 9 (6-17) Choose Most Often outlets, 6 (3-11) Choose Sometimes outlets and 35 (20-50) CLO outlets (Table 2) (consistent with other food environment literature (24,54) ). The median relative density of CLO outlets within 1600 m of schools was 64•7 % (60•8 %-72•9 %) (Table 2).…”
Section: Resultssupporting
confidence: 83%
“…There were median (IQR) 46 (33-77) food outlets within 1600 m of schools, ranging from eleven to 124 outlets. There were 9 (6-17) Choose Most Often outlets, 6 (3-11) Choose Sometimes outlets and 35 (20-50) CLO outlets (Table 2) (consistent with other food environment literature (24,54) ). The median relative density of CLO outlets within 1600 m of schools was 64•7 % (60•8 %-72•9 %) (Table 2).…”
Section: Resultssupporting
confidence: 83%
“…Young people spend most of their time either at home or in school, making these two settings central to their daily lives and activity spaces. Despite this, studies have rarely quantified the effect of exposure to both settings considered together ( 26 , 32 , 36 , 39 ) , hampering exploration of the cumulative impact of multiple environmental exposures occurring across the day that may affect diet. A second limitation is an almost exclusive focus on environmental exposures based upon the presence of specific types of food retailers in a given area (i.e.…”
mentioning
confidence: 99%
“…Research studies conducted in high and middle income nations have shown that one’s food environment plays a role in influencing diet quality and obesity risk [ 12 , 13 , 14 , 15 ]. Availability of healthy and unhealthy food options affects purchase decisions and consumption patterns among children and adults [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%